The Nantucket Sea Monster : A Fake News Story - Darcy Pattison (New York, United States Mims House, 2017)
d
Keywords: Circle Time + PY-UOI - How we express ourselves; Circle Time Book - Technology / Infoliteracy / Cybersafety -- Circle Time Book - Technology / Infoliteracy / Cybersafety